Beyond Statistical Ritual: Theory in Psychological Science. (July 2021) - Proulx, Travis; Morey, Richard D.
More than 40 years ago, Paul Meehl (1978) published a seminal critique of the state of theorizing in psychological science. According to Meehl, the quality of theories had diminished in the preceding decades, resulting in statistical methods standing in for theoretical rigor. In this introduction to the special issue Theory in Psychological Science, we apply Meehl's account to contemporary psychological science. We suggest that by the time of Meehl's writing, psychology found itself in the midst of a crisis that is typical of maturing sciences, in which the theories that had been guiding research were gradually cast into doubt. Psychologists were faced with the same general choice when worldviews fail: Face reality and pursue knowledge in the absence of certainty, or shift emphasis toward sources of synthetic certainty. We suggest that psychologists have too often chosen the latter option, substituting synthetic certainties for theory-guided research, in much the same manner as Scholastic scholars did centuries ago. Drawing from our contributors, we go on to make recommendations for how psychological science may fully reengage with theory-based science.